Knowledge and attitude towards antibiotic use and awareness on antibiotic resistance among older people in Malaysia: Antibiotic and elderly - Sien, Koo Hui; Omar, Marhanis Salihah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Antibiotic resistance is a significant global health concern. The challenges of antibiotics usage among elderly include antibiotic overuse, antibiotic resistance, dosing of antibiotics and adverse effects. This study aimed to evaluate the knowledge and attitude towards antibiotics usage among the elderly as well as the awareness on antibiotic resistance. A prospective cross-sectional study was conducted in outpatient department of a tertiary hospital in Malaysia from September 2016 to November 2016 using researcher-assisted and validated questionnaires. A total number of 250 elderly patients were recruited and majority of them (n=152, 60.8%) had moderate level of knowledge, with a median (IQR) score of 6.00(3.00) out of 12 points and positive attitude with a median (IQR) score of 7.00(1.00) out of 8 points. There was a positive correlation between knowledge and attitude scores (r = 0.335, p<0.001). Generally, awareness on antibiotic resistance was low as majority of the elderly respondents were not familiar (n=182, 71.8%) with the term “antibiotic resistance” and had never hear or read about antibiotic resistance before (n=150, 60.0%). In conclusion, majority of the elderly respondents had moderate level of knowledge and positive attitude towards antibiotics, implying the necessities of having public awareness campaigns to rectify the incomplete understanding of antibiotic use.